Healthcare use at the end of life of patients with congenital heart disease: does heart failure matter?. (2nd July 2022) - Van Bulck, L; Goossens, E; Morin, L; Luyckx, K; Ombelet, F; Willems, R; Budts, W; De Groote, K; De Backer, J; Moniotte, S; De Hosson, M; Marelli, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Research Foundation Flanders (to PM, EG, and LVB) European Society of Cardiology (Nursing Training Grant to LVB) Background: Heart failure (HF) is a common cause of morbidity and mortality in patients with congenital heart disease (CHD). Although limited in scope, previous studies suggest that patients with heart failure follow a specific end-of-life trajectory with episodes of serious complications, which may impact the patterns of care as death approaches. Aims: The study aims to identify differences in characteristics and patterns of care in the last year of life in deceased CHD patients with and without HF. Methods: This retrospective study used data of deceased adult patients included in the BELgian COngenital heart disease Database combining Administrative and Clinical data (BELCODAC). To describe patterns of care in the last year of life, we captured information about hospitalisations, emergency department visits, and visits to the general practitioner using nomenclature codes. Heart failure was identified as having HF as cause of death and/or at least one prescription of a loop diuretic in the last year of life. Sensitivity analyses with a stricter definition for HF (HF as cause of death or ≥ 1 prescription of a loop diuretic combined with a prescription of digoxin, dopamine, dobutamine, other non-glycoside stimulants, metoprolol, bisoprolol, carvedilol, aldosterone antagonists, ACE inhibitors or ARBs) were performed as well. Results: During the period 2007–2016, 390 adults with CHD died, of which 170 patients with HF (44%). Patients with HF were older, died more often due to a cardiovascular cause of death, and had more complex heart lesions, compared to patients without HF (Table 1). While the number of emergency department visits and hospitalisations in the last year was similar, patients with HF had almost twice as much monthly visits at the general practitioner in their last year of life (Table 1). As shown in Figure 1, the mean number of hospitalisations and emergency department visits increased in a similar fashion throughout the last year of life, but the pattern of general practitioner visits was substantially different for patients with and without HF. The sensitivity analyses, in which a stricter definition for HF was used, yield very similar results. In these analyses, the difference in mean monthly hospitalisations was also significant between the two groups. Conclusions: This study shows clinically important differences in characteristics and patterns of care of deceased patients with CHD with and without heart failure. Patients with HFhave different needs and should receive a tailored approach at the end of life. Future research is needed to understand these differences and investigate these patients' end-of-life care needs in more detail. Funding acknowledgments: This work was supported by Research Foundation Flanders; European Society of Cardiology; the King Baudouin Foundation; the National Foundation on Research in Pediatric Cardiology; and the Swedish Research Council for Health, Working Life and Welfare-FORTE.